Effectiveness of Silver Nanoparticles (AgNPs) Synthesized Using Waste Lime Peel Extract (Citrus aurantifolia Swingle) Against Bacteria Causing Nosocomial Infections - Ainun Najib; eka yunita wulandari; mamluatul faizah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Nosocomial infections remain a serious challenge because they increase morbidity, mortality, hospitalization length, and healthcare costs. Rising bacterial resistance to conventional antibiotics has encouraged exploration of alternative antibacterial agents. Silver nanoparticles synthesized through green methods have attracted attention because of their broad-spectrum activity, while lime peel waste offers a natural source of reducing and stabilizing compounds. Methods: This true experimental study used a post-test control group design. Silver nanoparticles were biosynthesized using lime peel waste extract and characterized by visual color change, UV-Vis spectrophotometry, Fourier Transform Infrared spectroscopy, and Scanning Electron Microscopy. Antibacterial activity against Pseudomonas aeruginosa was evaluated in vitro by disc diffusion at concentrations of 25, 50, 75, 100, and 125 μg/mL, with controls. Data were analyzed using Shapiro-Wilk, Levene’s test, and One-Way ANOVA. Results: The biosynthesis process produced a visible color change, confirming nanoparticle formation. Characterization showed a maximum absorption peak around 380 nm, functional groups associated with phytochemical reduction and capping, and spherical particles ranging from 13 to 53 nm with an average size of 31 nm. All tested concentrations inhibited Pseudomonas aeruginosa and were classified as strong. The largest inhibition zone among nanoparticle groups was observed at 125 μg/mL (18.20 ± 0.81 mm), although levofloxacin produced the greatest inhibition. Statistical analysis showed significant differences among treatments (p < 0.05). Conclusions: Lime peel waste extract was successfully used for green synthesis of silver nanoparticles with strong antibacterial activity against Pseudomonas aeruginosa. These findings indicate potential for developing environmentally friendly antibacterial agents for nosocomial infection control